BRAND TRUST AND CUSTOMER LOYALITY IN SERVICE COMPANIES HEALTH - Munawaroh, Emi; Rianto (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2022)
Introduction: This study was conducted to examine the effect of trust in brand (brand characteristic, company characteristic, and customer - brand characteristic) on brand loyalty in hospital patients. Methods: The method used in this study is a quantitative descriptive research method with a multiple linear regression analysis approach using 100 respondents who have used the services of RSUD Dr. Sudirman Kebumen. Results: The results of this study indicate that trust in brand has a positive effect on brand loyalty, either partially for each dimension of brand characteristic, company characteristic, and customer-brand characteristic or simultaneously. Furthermore, customer-brand characteristic is the dominant variable even though the difference is not great. Therefore, it can be concluded that, in building brand loyalty, it requires building trust from the brand with characteristics starting from the brand itself, and how the patient's relationship with the brand is established. Conclusion and suggestion The author finds that building brand loyalty in service companies, especially health services at regional companies, requires good brand trust management. This is a new finding because previous research has focused on goods industry. Brand loyalty is focused not only on a tangible product industry, but even health service companies need good brand awareness, especially trust, to be able to maintain customer loyalty to the brand.